Glenn Gould: A Life and Variations - Friedrich, Otto (New York Random House, 1989)
He was a virtuoso of the piano who inspired an almost religious fervor in his fans, yet he hated performing and left the concert stage forever at the age of 31. He was a tireless advocate of the technology of recording, an artist who looked forward to a time when mere musicians would be rendered obsolete. He was a notorious -- and, some thought, a deliberate -- eccentric, who muffled himself in scarves and gloves, liberally dosed himself with pills, and once sued Steinway & Sons because one of its employees had shaken his hand too roughly. He lived in hermetic solitude and liked to call himself "the last Puritan," but those who watched Glenn Gould play piano saw an eroticism so intense it was almost embarrassing.Drawing on extensive interviews and on archival materials that were previously inaccessible. Otto Friedrich has written a biography of exemplary depth and stylishness. Ranging over Gould's brief but spectacular public career and his prodigious exploits as teacher, author, and lecturer, his public opinions and his intensely private life. Glenn Gould; A Life and Variations does justice to a multifaceted and perverse genius.
Keywords: Gould, Glenn -- 1932-1982; 20th Century (1901-2000); Pianist; Biography; Canada